The influence of effective communication principles towards organizational task conflict among employees : A case study in Kuala Lumpur Law Courts / Harlina Ambar and Safaezzah Sabaruddin - Ambar, Harlina; Sabaruddin, Safaezzah (Faculty of Administrative Science and Policy Studies, 2012)
Differences opinion and the resulting conflict are common to any organization or community group. One of the most common factors of conflict is lack of communication. . By expressing our desires, feelings, thoughts and opinions clearly and effectively can increase in communication hence will reduce in task conflict occurrence. Thus, “effective communication is a building block of successful organizations” and communication acts as organizational blood. The objective of this research is to study the relationship between face to face conversation, situational based leadership and active listening. A total respondent of 181 support staffs of Kuala Lumpur Law Court were selected to fill the sets of questionnaires that consist of 5 sections which are Demography (Section A), Face to Face Conversation (Section B), Situational Based Leadership (Section C), Active Listening (Section D) and Organizational Task Conflict (Section E). The data was analyzed with Pearson Correlation and Linear Regression Analysis of Statistical Package for Social Sciences (SPSS) version 18.0. The result indicates that there were positive correlation between face to face conversation, situational based leadership and active listening towards organizational task conflict. In addition, active listening has been found to be the most influence variable of effective communication principles towards organizational task conflict. As a conclusion, this study will investigate the most influence variable of effective communication principles towards organizational task conflict.